Assessment of Peri-Procedural Myocardial Injury by High-Sensitivity Troponin-I Levels after Successful Elective Percutaneous Transluminal Coronary Angioplasty - Toru, Fahad Khan; Shabbir, Muhammad; Ahmed, Iftikhar; Shabbir, Aneela; Paiker, Sarwat; Arif, Zeeshan; Ahmad, Zeeshan; Siddiqui, Abdul Hameed (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the incidence of Peri-Procedural Myocardial Injury (PMI) after elective, successful Percutaneous Transluminal Coronary Angioplasty (PTCA) as assessed by High Sensitivity troponin-I (HS-Trop-I) levels, and to find out association between PMI and clinical, angiographic and procedural variables.Study Design: Analytical Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan, from Dec 2022 to Jun 2023.Methodology: Total one hundred and thirty-one cases were included using consecutive sampling technique. Patients with stable angina and having at least one positive stress test, baseline pre-PCI cardiac troponin level below the 99th percentile upper reference limit (normal baseline troponin), and a target lesion with a stenosis of >70% on qualitative angiography were included in study. Patients were divided into two groups; (Group-I=HS-Trop-I>40ng/L and Group-II=HS-Trop-I≤40 ng/L). Independent samples t-test and Pearson’s Chi-square test were applied to compare the study variables among study groups and p0.05). Total stent length and max balloon time, were significantly higher in the group-I (50.73±25.19mm vs 31.13±17.83mm; 26.80±7.51sec vs 22.42±5.94sec respectively) (p